2012
DOI: 10.1097/mph.0b013e318249ad34
|View full text |Cite
|
Sign up to set email alerts
|

Patient-related Barriers to Cancer Pain Management in Jordan

Abstract: Barriers to cancer pain management are prevalent among cancer patients around the world, which may hinder patients from receiving adequate pain treatment. However, no study has examined the barriers to cancer pain management among Jordanian cancer patients and thus this study was conducted to fill this gap. Fifty cancer patients completed the Barriers Questionnaire. It was found that patients held high level of concerns (mean of Barriers Questionnaire = 2.58, SD = 0.54). In addition, fear of addiction, fear of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
1
10
1
Order By: Relevance
“…The items that directly affected the patients’ attitude scores included “Analgesics should be given when there is a real need”, “Patients will become addicted to analgesics and should try not to use it unless they are unable to bear the pain”, “If you take analgesics when you have mild pain, it might not work when the pain becomes worse”, and “Using analgesics can harm the liver and kidneys”. This finding was similar to the research results of Mohammad et al (27), Tosun et al . (30), and Sun et al .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The items that directly affected the patients’ attitude scores included “Analgesics should be given when there is a real need”, “Patients will become addicted to analgesics and should try not to use it unless they are unable to bear the pain”, “If you take analgesics when you have mild pain, it might not work when the pain becomes worse”, and “Using analgesics can harm the liver and kidneys”. This finding was similar to the research results of Mohammad et al (27), Tosun et al . (30), and Sun et al .…”
Section: Discussionsupporting
confidence: 93%
“…Scores of 2.5 and higher on the BQT indicated a poor attitude and a high level of attitude barriers regarding cancer pain management (27). The patient attitude score in this study (2.96±0.49) indicated that the general attitude of the cancer patients towards pain management was poor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, studies conducted in other countries, including Denmark, 24 China (specifically Hong Kong), 25 Iceland, 26 Jordan, 27 and Lithuania, 28 have reported consistently higher barrier scores than those reported by that first validation study. Those higher scores are consistent with the results of our previous study, which focused on Korean cancer patients.…”
Section: Discussioncontrasting
confidence: 47%